Regional control problem for distributed bilinear systems: approach and simulations - Ztot, Karima; Zerrik, El Hassan; Bourray, Hamid (Zielona Góra: Uniwersytet Zielonogórski)
This paper investigates the regional control problem for infinite dimensional bilinear systems. We develop an approach that characterizes the optimal control and leads to a numerical algorithm. The obtained results are successfully illustrated by simulations.
Keywords: distributed systems; bilinear systems; regional controllability; regional optimal control problem